Theology and difference : the wound of reason - Lowe, Walter James, 1940- (Bloomington : Indiana University Press, 1993)
Theology and Difference reconceives the options confronting modern theology and investigates the disputed questions that underlie it. Pressing beyond the ready-made enlightenment offered by the subject-object framework, Walter Lowe uncovers a number of remarkable convergences between the contemporary philosopher Jacques Derrida and the early twentieth-century theologian Karl Barth. --From publisher's description.
Introduction : violence and reason -- Qualitative difference : Barth's Epistle to the Romans -- Truth and contextualization : Freud, Husserl, Derrida -- The Kantian opening -- The otherness of the ethical -- The ethics of otherness.
Includes bibliographical references (pages 165-177) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Theology -- Methodology; Theology; Theodicy; Deconstruction; Faith and reason; Deconstructivism (Architecture); Théologie -- Méthodologie.; Théologie.; Théodicée.; Déconstruction.; Foi et raison; Déconstructivisme (Architecture); theology; Deconstructivist; deconstruction (theory); RELIGION -- Christianity -- General; RELIGION -- Cults; Deconstruction; Faith and reason; Theodicy; Theology; Theology -- Methodology; Theodicee; Godsdienstfilosofie